2018
DOI: 10.29390/cjrt-2018-017
|View full text |Cite
|
Sign up to set email alerts
|

Basic spirometry testing and interpretation for the primary care provider

Abstract: Spirometry testing plays an important role in the diagnosis and management of COPD and asthma in the primary care setting. Verifying the accuracy of the spirometer, using accurate patient demographics and appropriate reference equations, and ensuring the competency of testing personnel are key components of spirometry test interpretation. Spirometry testing plays an important role in the diagnosis and management of lung disease in the primary care setting. Spirometry interpretation should include an assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
0
22
0
3
Order By: Relevance
“…None of the patients had previous lung disease or environmental exposure associated with the occurrence and magnitude of their injuries during the follow-up period; thus, the development of TSP-HAM was considered to be the only associated factor. Although previous reports have described pulmonary involvement in individuals infected with HTLV-1 regardless of their clinical characteristics [ 12 , 35 , 36 ], most studies have found differences between patients with clinical features of inflammatory diseases related to asymptomatic carriers of viral infection [ 7 , 32 , 37 , 38 ] with a higher frequency of pulmonary involvement among individuals with TSP-HAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the patients had previous lung disease or environmental exposure associated with the occurrence and magnitude of their injuries during the follow-up period; thus, the development of TSP-HAM was considered to be the only associated factor. Although previous reports have described pulmonary involvement in individuals infected with HTLV-1 regardless of their clinical characteristics [ 12 , 35 , 36 ], most studies have found differences between patients with clinical features of inflammatory diseases related to asymptomatic carriers of viral infection [ 7 , 32 , 37 , 38 ] with a higher frequency of pulmonary involvement among individuals with TSP-HAM.…”
Section: Discussionmentioning
confidence: 99%
“…The downward trend in VC, FVC, and FEV1, with the maintenance of normal FEV1/FVC values may indicate the development of restrictive lung disease; however the restriction must be confirmed by measuring lung values and documenting total lung capacity below normal limits [ 38 ]. The MVV measure is related to the level of physical activity in daily life, applied to individuals with chronic obstructive pulmonary disease [ 39 ], and the tendency of decreased values in HTLV-1 positive individuals may be related to the development of motor changes related to myelopathy associated with HTLV-1 infection or tropical spastic paraparesis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies went beyond questionnaire-based self-reported experience of respiratory symptoms and employed spirometry testing, which is a lung function test used to assess how well a person’s lungs work by measuring how much air they inhale, how much and how quickly they exhale [ 47 ]. It is also one of the most commonly used methods to diagnose respiratory conditions such as asthma and chronic bronchitis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also one of the most commonly used methods to diagnose respiratory conditions such as asthma and chronic bronchitis [ 48 ]. However, this approach is challenging because the results of spirometry testing are dependent on proper calibration of the instrument, proper training of personnel who are conducting the test, and selecting an appropriate reference population [ 47 ]. Despite these challenges, current practice dictates that spirometry testing is the most appropriate tool to differentiate between normal lung function and obstructive and restrictive respiratory diseases; however, it requires proper handling of the data and use of the spirometer to provide accurate results.…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry was considered to be suggestive of asthma in undiagnosed patients when the forced expiratory volume in the first second predicted value was <80% [11]. In diagnosed asthma patients, a forced expiratory volume in the first second <80% was considered moderate disease and ≤60% as severe disease.…”
Section: Methodsmentioning
confidence: 99%